(495) basic principles of the economic system of planning and managing of national economy in socialist countries المبادئ الأساسية للنظام الاقتصادي لتخطيط وإدارة الاقتصاد الوطني في البلدان الاشتراكية - sack, kurt; linse, hermann (the institute of national planning, 2018)
This study examines the fundamental principles of the new economic system for planning and managing the national economy in socialist countries, focusing on the institutional and administrative mechanisms designed to balance centralized planning with economic efficiency requirements. The study is based on the assumption that traditional centralized economic management encountered limitations regarding resource allocation efficiency and productivity performance, thereby creating a need for more flexible approaches to economic administration. The study explains that the proposed economic system does not seek to eliminate centralized planning; rather, it attempts to redefine the relationship between central planning authorities and productive institutions. Within socialist economic systems, planning is regarded as a strategic instrument for directing economic and social development. However, its effectiveness depends on the capacity of economic institutions to respond efficiently to production conditions and changing economic requirements. The study further addresses the role of economic indicators in managing productive activities, including productivity, costs, profits, economic efficiency, and resource utilization measures. Particular attention is given to quantitative indicators and economic tools that can assist decision-makers in improving allocation procedures and balancing national objectives with operational requirements at the enterprise level. In addition, the study discusses the relationship between planning systems and economic incentives, arguing that improvements in material and administrative incentive mechanisms may contribute to stronger economic performance and greater institutional efficiency. The analysis also emphasizes the importance of information systems and performance evaluation methods for monitoring economic outcomes and measuring developmental achievements. The study concludes that the effectiveness of the new economic system depends largely on the integration of strategic planning with flexible economic management practices capable of improving resource utilization and supporting long-term economic growth and development.